Inova????o para exporta????o: um estudo de caso no setor de alimentos - Lopes, Ana Maria Motta Garcia (2006)
This paper aimed at studying the innovation and internationalization processes of a Brazilian enterprise in the food processing sector, in the light of the behavioral and economic theories of the internationalization of firms, and the technological innovation strategies and models. The selected firm was SADIA, which is the leader in the domestic market, and began export activities back in 1975. Presently it has a strong role in the international market, due to its continuous activities of new product development and adaptation to different cultures in different countries. The research method followed was the case study approach, which allowed for the deep understanding of the company??s strategy and trajectory in search of the external market. The results show that innovation is a key factor for SADIA, which annually releases about 90 new products for the local market, and around 30 for the foreign markets.